2011
DOI: 10.1007/s13530-011-0071-8
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition of aquatic plant caused by silver and titanium oxide nanoparticles

Abstract: Emerging nanomaterials are of great concern to aquatic environment. The inhibitory effects of silver nanoparticles (Ag-NP) and titanium oxide nanoparticles (TiO 2 -NP) on the growth of aquatic plant duckweed were evaluated. Lemna paucicostata was used as a test organism, and the test method was followed by the OECD test guideline 221. Ag-NP (50 nm) and TiO 2 -NP (2-3 nm) inhibited the growth of Lemna in different manner and the EC50s were calculated as 13.8 and 538.5 ppm, respectively. The LOECs of Ag-NP and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(31 citation statements)
references
References 28 publications
1
24
1
3
Order By: Relevance
“…However, despite no information is available about the concentrations of these NMs in the environmental compartments, in our opinion, concentrations above this level will have no ecological relevance. In fact, Kim et al (2011) andSong et al (2012) found that nano-TiO 2 can cause growth inhibition in two species of Lemna but the concentrations tested were much higher than those tested in our study. Further, these authors have tested nano-TiO 2 with 2-3 and 5-10 nm in size, what may explain the difference in toxicity results.…”
Section: Discussioncontrasting
confidence: 72%
“…However, despite no information is available about the concentrations of these NMs in the environmental compartments, in our opinion, concentrations above this level will have no ecological relevance. In fact, Kim et al (2011) andSong et al (2012) found that nano-TiO 2 can cause growth inhibition in two species of Lemna but the concentrations tested were much higher than those tested in our study. Further, these authors have tested nano-TiO 2 with 2-3 and 5-10 nm in size, what may explain the difference in toxicity results.…”
Section: Discussioncontrasting
confidence: 72%
“…Studies are presently emerging concerning the toxicity of TiO 2 -NPs, especially toward freshwater algae and invertebrates. Growth inhibition of another Lemna species has been observed by Kim et al [13], but at a concentration above 250 mg/L TiO 2 -NPs, which represents a much higher nano-TiO 2 concentration than is currently expected to be present in aquatic ecosystems [14]. The same finding applies to current toxicity data for freshwater invertebrates [11].…”
Section: Introductionsupporting
confidence: 66%
“…For duckweed, the Ag-NPs toxicity was observed at the 14 ppm concentration, whereas the lowest concentration in which toxicity changes were observed (chlorosis and necrosis) was 1 ppm of Ag-NPs. The Ag-NPs bioaccumulation in the eyelashes and body after 5 days exposure with 10, 20, and 40 ppm concentrations is 55%, 65%, and 19%, respectively (Kim et al 2011). Other literature reports show that the 0.005 ppm Ag-NPs concentration can lead to the 80% inhibition of the duckweed growth (Gubbins et al 2011).…”
Section: Metal Nanoparticlesmentioning
confidence: 90%
“…Ag-NPs can also be used as water disinfectant due to their strong biocidal effect observed in organisms such as Escherichia coli (Choi et al 2008, Cho et al 2005, Sondi and Salopek-Sondi 2004, Wang et al 2012, Radziga et al 2013, Staphylococcus aureus (Choi et al 2008), Caenorhabditis elegans , Marinobacter sp. (Sinha et al 2011), Lemna minor (Gubbins et al 2011, Kim et al 2011, Bacillus subtilis , Wang et al 2012, Saccharomyces cerevisiae, Trichosporon beigellii, Candida albicans ), Ceriodaphnia dubia (Glover and Wood 2004), Daphnia magna (Glover and Wood 2004, Jo et al 2012, Bianchini et al 2005, Blinova et al 2013, Thamnocephalus platyurus (Blinova et al 2013), Agrobacterium tumefaciens (Wang et al 2012), and Pseudomonas aeruginosa, and Serratia proteamaculans (Radziga et al 2013).…”
Section: Metal Nanoparticlesmentioning
confidence: 99%